Frequency of Pelvic Inflammatory Disease in Infertile Patients - Raisham Saleem, Saadia Mir, Shafia Zaib Mir, Ayesha Manzoor (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Frequency of pelvic inflammatory disease in women presenting with infertility Study design: Cross sectional research Setting: Obstetrics/Gynaecology Deptt., Services Hospital, Lahore from 20-10-2017 to 20-04-2018. Methods: One hundred married females with Infertility (Primary/Secondary) were included in the study. Patients with H/o intrauterine contraceptive devices usage, diabetes, male factor Infertility and H/O pelvic surgery were excluded. All women were taken complete history and detailed physical and gynecological examination and HVS was sent to laboratory for culture. Results: Age was from 20 to 35 years with mean ± SD 29.41±2.35 yrs, mean±SD of weight 70.09±12.66kg, mean±SD height 1.54±0.09 meters, mean ± SD of BMI 29.67±5.09 Kg/m2 and mean±SD duration of Infertility was 2.5±0.97 years. Majority of the patients were from 0-2 parity (92%). Primary infertility was found in 64% women while secondary infertility was 36%. Pelvic Inflammatory Disease was found in 27% patients. Conclusion: Tubal damage before and during the index episode of PID is correlated with infertility.